3(x+12)=2x+51

Simple and best practice solution for 3(x+12)=2x+51 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+12)=2x+51 equation:


Simplifying
3(x + 12) = 2x + 51

Reorder the terms:
3(12 + x) = 2x + 51
(12 * 3 + x * 3) = 2x + 51
(36 + 3x) = 2x + 51

Reorder the terms:
36 + 3x = 51 + 2x

Solving
36 + 3x = 51 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
36 + 3x + -2x = 51 + 2x + -2x

Combine like terms: 3x + -2x = 1x
36 + 1x = 51 + 2x + -2x

Combine like terms: 2x + -2x = 0
36 + 1x = 51 + 0
36 + 1x = 51

Add '-36' to each side of the equation.
36 + -36 + 1x = 51 + -36

Combine like terms: 36 + -36 = 0
0 + 1x = 51 + -36
1x = 51 + -36

Combine like terms: 51 + -36 = 15
1x = 15

Divide each side by '1'.
x = 15

Simplifying
x = 15

See similar equations:

| 2(x+3)-6=5x+12 | | 14-5x=-7x+14 | | 3.61n=8+2.476n | | -10y=-130 | | 14=-15a+4a | | 7x-3x+9=12+x | | x^2+4s=27 | | 15=7+2u | | 5(x+2)-3=2 | | 6-9*0=-21 | | 5(3x-1)=4(3x-2) | | 6-9*3=-21 | | -6-9*9=-21 | | 6-9*-5=-21 | | 5(x+4)-x=16 | | -91=-7(6+5) | | 3x-19=30 | | -91=-7(8+5) | | 5x-1+3x=11+4x | | -91=-7(-7+5) | | (2x-5)(2x-5)=(x-1)(x-1) | | -91=-71(-5+5) | | 200=49-u | | 88=8 | | -2.8x=-5.6 | | 8*9+7=39 | | 8*-2+7=39 | | 8*3+7=39 | | a(a-b)+2a=3+a(a-2) | | x^5-9x^4+26x^3-34x^2+25x-25=0 | | 8*-7+7=39 | | 18sint=0 |

Equations solver categories